Genealogi Teologi Nahdlatul Ulama - Qa’im, Suis (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
NU, the largest social and religious organization in Indonesia, has undergone many changes since its very inception decades ago. But the essence of the organization remains the same, namely its theological doctrine and âideologicalâ inclination toward the Sunna. This paper tries to speak of the struggle of NU in this changing era to remain as it is. It traces the theological genealogy of the organization, and how this theology has been transformed from time to time to meet the demands of Indonesian setting. Here NU is understood as a dynamic religious organization capable of translating certain theology and ideology into a totally different look. Hence, although it was originated in the theology of al-Asyâariyyah and al-Maturidiyah, NU was not at all representing any of these two Middle Eastern theologies. Unlike the two, NU emphasizes theoretically the idea of justice, moderation, and tolerance while practically upholding the adaptive and adoptive attitude toward local customs and traditions.